2005
DOI: 10.1088/0953-8984/17/8/009
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic features of dimer and dangling bondE′ centres in amorphous silica

Abstract: We performed first-principle embedded cluster calculations of the hyperfine parameters, g-tensors and optical excitation energies for the dimer and backprojected configurations of the E centre in amorphous silica. The optical transition energies of these defects are calculated for the first time. We predict a strong optical transition at about 6.3 eV for the dimer configuration and a relatively weak transition at 5.6 eV for the back-projected configuration of the E centre. These predictions could be used for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…Moreover, if we restrict the average to the lowest-energy configurations, i.e., d SiSi 2.9Å, the g principal values will be ∼400 ppm larger: g 1 = 2.0023, g 2 = 2.0027, and g 3 = 2.0033, with a std of 400 ppm. The former average g values are compatible with the results of previous investigations where a hybrid functional (Becke threeparameter Lee-Yang-Parr) and localized basis sets were used but only a few dimer configurations were analyzed [28,32]. It is also worth noting that simply averaging g values over the investigated configurations, as done in Table II, does not properly convey the most relevant information of Fig.…”
Section: E δ Vs Si 2 Dimerssupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, if we restrict the average to the lowest-energy configurations, i.e., d SiSi 2.9Å, the g principal values will be ∼400 ppm larger: g 1 = 2.0023, g 2 = 2.0027, and g 3 = 2.0033, with a std of 400 ppm. The former average g values are compatible with the results of previous investigations where a hybrid functional (Becke threeparameter Lee-Yang-Parr) and localized basis sets were used but only a few dimer configurations were analyzed [28,32]. It is also worth noting that simply averaging g values over the investigated configurations, as done in Table II, does not properly convey the most relevant information of Fig.…”
Section: E δ Vs Si 2 Dimerssupporting
confidence: 83%
“…It is supposed to arise either from an interaction of an unpaired electron in a sp 3 -like orbital delocalized over four or five nearby 29 Si, or from an ionized single oxygen vacancy with the unpaired electron shared nearly equally by the two neighboring Si atoms (Si 2 dimer center). Though several theoretical works [17,26,32,33] support the Si 2 dimer hypothesis, they do not explain the intensity ratio between the main EPR resonance line and the 10 mT hyperfine doublet that seems to be better explained by assuming an E center involving at least four Si atoms [31,34]. Richard et al [35] have shown that for a positively charged oxygen vacancy, the dimer configuration appears to be the lowestenergy configuration with an 80% probability, in agreement with previous theoretical investigations [29].…”
Section: Introductionmentioning
confidence: 68%
“…The property of having two stable configurations is also referred to as 'bi-stability' and maybe linked to some unexpected behavior of defects in microelectronic transistors. As such, it was the subject of intensive discussions but has been confirmed by several independent groups [49][50][51][52][53][54][55]. Looking from a device perspective, it has been shown that the oxygen vacancy easily reacts with a hydrogen and forms a defect called hydrogen bridge [7,56], which has a defect level within the SiO 2 bandgap.…”
mentioning
confidence: 93%
“…For instance, the P b center has been intensively examined [45] and its reactions with atomic and molecular hydrogen considered in [46,47]. Furthermore, the positively charged oxygen vacancy in SiO 2 was found to be stable in two configurations where one of them could be related to the E center [48][49][50]. The property of having two stable configurations is also referred to as 'bi-stability' and maybe linked to some unexpected behavior of defects in microelectronic transistors.…”
mentioning
confidence: 99%
“…[15][16][17][18] Since its first observation, the microscopic model for the E δ center has been hotly disputed. [18][19][20] At variance to the other E centers, the E α center possesses an orthorhombic g matrix. The generally recognized experimental hyperfine splittings for E γ , E α and E δ are 42, 49 and 10 mT, respectively.…”
Section: Introductionmentioning
confidence: 99%